(untitled) (Asian Journal of Medical and Biological Research, 2020)
Atherosclerosis is a chronic inflammatory state, which arise from the imbalance in lipid metabolism. Over the last decade, studies have showing the association of macrophages with this maladaptive immune response. Macrophages differentiated from monocytes and populate at the growing atherosclerotic lesions. At the lesion site by accumulating lipid they actively participate in the formation of atherosclerotic plaque. These plaques are very susceptible to rupture which can lead to myocardial infarction or stroke. In future more studies are needed to classify different macrophage populations according to their phenotypic and functional characteristics to identify their roles in the pathogenesis of atherosclerosis. This review highlights several aspects of macrophages activation, diversity, recruitment, and foam cell formation in atherosclerosis. Asian J. Med. Biol. Res. September 2020, 6(3): 366-374